ERF: an ETS domain protein with strong transcriptional repressor activity, can suppress ets-associated tumorigenesis and is regulated by phosphorylation during cell cycle and mitogenic stimulation. - Sgouras, D N (1995)
ERF (ETS2 Repressor Factor) is a novel member of the ets family of genes, which was isolated by virtue of its interaction with the ets binding site (EBS) within the ETS2 promoter. The 2.7 kb ubiquitously expressed ERF mRNA encodes a 548 amino acid phosphoprotein that exhibits strong transcriptional repressor activity on promoters that contain an EBS. The localization of the DNA-binding domain of the protein at the N-terminus and th repression domain at the C-terminus is reminiscent of the organization of ELK1-like members of the ets family; however, there is no significant homology between ERF and ELK1 or any other ets member outside the DNA-binding domain. The repressor activity of ERF can antagonize the activity of other ets genes that are known transcriptional activators. Furthermore, ERF can suppress the ets-dependent transforming activity of the gag-myb-ets fusion oncogene of ME26 virus. Although ERF protein levels remain constant throughout the cell cycle, the phosphorylation level of the protein is altered as a function of the cell cycle and after mitogenic stimulation. The ERF protein is also hyperphosphorylated in cells transformed by the activated Ha-ras and v-src genes and the transcription repressor activity of ERF is decreased after co-transfection with activated Ha-ras or the kinase domain of the c-Raf-1 gene, indicating that ERF activity is probably regulated by the ras/MAPK pathway. Consistent with the in vivo phosphorylation and inactivation by ras, ERF is efficiently phosphorylated in vitro by Erk2 and cdc2/cyclin B kinases, at sites similar to those detected in vivo. Furthermore, a single mutation at position 526 results in the loss of a specific phosphopeptide both in in vivo and in vitro (by Erk2) labeling. Substitution of Thr526 for glutamic acid also decreases the repression ability of ERF. Our data suggest a model in which modulation of ERF activity is involved in the transcriptional regulation of genes activated during entry into G1 phase. Obstruction of the ERF repressor function by the transactivating members of the ets family of genes (i.e.gag-myb-ets) may be essential for the control of genes involved in cell proliferation and may also underlie their tumorigenic effects.